Perbedaan Hasil Belajar Siswa Kelas XI SMA Negeri 9 Palu yang Mengikuti Model Pembelajaran Berbasis Masalah Dan Model Inkuiri Untuk Gaya Belajar Yang Berbeda - Rusmin Y. Ma’bud; Mustamin Mustamin; Baso Amri Mursyid (Universitas Tadulako, 2016)
This research aimed to describe difference of students’ learning outcome between students that enrolled problem-based learning and inqury learning model for two conditions of learning styles. The research was conducted at SMA Negeri 9 Palu used quasy-experiment method with 2 ´ 2 factorial. The two learning models were as two factors and learning styles were two factors, i.e field independent and field dependent. The research instruments were learning styles test and mathematics conceptual understanding test. Sample of the research was 42 students at Class XI-IPA of SMA Negeri 9 Palu and it was determined by random sampling. Research data analysis used two-path analysis. Results of the data analysis showed that (for α = 0,05): (1) there was a significant difference of mathematics learning outcome of students who enrolled problem-based learning model and students who enrolled inquiry model; (2) there was a significant difference of mathematics learning outcome between students with independent and dependent of learning style; (3) there was an interaction between the learning models and the learning styles and their effect to the mathematics learning outcome; and (4) The students’ learning outcome for the problem-based learning was better than the students’ learning outcome for the inquiry learning model, for the two learning styles.